Study of Machining of Inconel 825 Super Alloy Using Powder Mixed EDM Process. (2018) - Kumar, Sanjay; Kumar, Amit; Kumar, Vinay; Singh, N.K.
Abstract: Powder mixed electrical Discharge Machining (PMEDM) plays vital role in machining process of some very difficult to machine materials. Inconel 825 are highly demanding materials for today's industries due to their unique properties. Properties like high creep resistance under high stress condition, high resistant to corrosion, good machinability, ductility, weldibility, low value of thermal expansion makes it durable for high speed aeroplanes and supersonic jets. In present work Inconel 825 (nickel alloy) which is widely used in aerospace industries, power plants, nuclear power plants, petro chemical, chemical rockets has been used as work piece and machined with using powder mixed electrical discharge machining process (PMEDM). Peak current (IP), gap voltage (GV), powder concentration (PC) and pulse on time (TON ) are opted as input experimental parameters. Whereas, surface roughness (SR) and material removal rate (MRR) are considered as output response parameters. Tool used during experiment is tungsten carbide. Tungsten carbide is hard materials in which wear is minimum. It could be concluded from the experiment that there is significant improvement in MRR as well as SR. Tool wear is negligible. Further, surface machined by PMEDM is compared with conventional EDM and analysed using field emission electron microscopy (FESEM) and RSM (response surface methodology). Images obtained by FESEM also confirm improvement in surface integrity. Moreover, less micro-crack, micro-holes and shallower craters were observed on the surface generated by PMEDM as compare to conventional EDM